Digital Social Revolution: How New Technologies Are Changing the Way We Interact and Build Communities - Bauer, Thomas (Raudhah Publisher, 2024)
The digital age has ushered in a profound transformation in social interaction and community building, driven by rapid advancements in technology. This article explores the impact of emerging technologies—such as artificial intelligence (AI), big data, and advanced communication platforms—on the way individuals connect and engage within their communities. Utilizing a qualitative approach, including literature review and library research, the study analyzes existing research and theoretical frameworks to understand these shifts. The findings highlight how new technologies have facilitated global connectivity, enabling more dynamic and diverse interactions. However, they also pose challenges, such as privacy concerns and the potential for superficial relationships. The paper further investigates how these technological changes influence community cohesion, civic participation, and social capital. By synthesizing insights from various sources, this study aims to provide a comprehensive overview of the ongoing digital social revolution and its implications for future social structures. The research underscores the need for ongoing examination of how technology shapes social norms and practices to better navigate and leverage these changes for enhanced community engagement and social well-being.